Clinical impacts of cerebral microbleeds in patients with established coronary artery disease. Issue 2 (February 2021) - Uemura, Yusuke; Shibata, Rei; Imai, Ryo; Ishikawa, Shinji; Takemoto, Kenji; Watarai, Masato; Murohara, Toyoaki
Abstract : Objective: Although cerebral microbleeds predict the occurrence and recurrence of cerebrovascular events in stroke patients, their clinical impacts are unclear in coronary artery disease patients. We aimed to investigate the clinical effect of the presence of cerebral microbleeds in patients with coronary artery disease receiving antithrombotic treatment. Methods: We included 447 coronary artery disease patients taking at least one thrombotic agent who underwent brain MRI. The association between the presence of cerebral microbleeds and incidence of major adverse cardiac and cerebrovascular events was investigated. Results: Cerebral microbleeds were identified in 18.7% of patients. Median follow-up duration was 1055 (interquartile range, 781–1172) days. Kaplan–Meier survival analysis demonstrated that patients with cerebral microbleeds had a higher incidence of major adverse cardiac and cerebrovascular events than those without (log-rank P  = 0.003). A multivariate Cox regression analysis revealed that the presence of cerebral microbleeds was independently correlated with the occurrence of major adverse cardiac and cerebrovascular events after adjusting for other classical risk factors of coronary artery disease (hazard ratio 1.965, 95% confidence interval 1.086–3.556, P  = 0.026). Hypertension was associated with the presence of cerebral microbleeds. The cut-off values to maximize the predictive power of SBP and DBP were 132 and 74 mmHg, respectively ( P  < 0.001). Conclusion: The presence of cerebral microbleeds predicts major adverse cardiac and cerebrovascular events in coronary artery disease patients receiving antithrombotic treatment. Evaluation of cerebral microbleeds and hypertension treatment complying with the established guidelines may be beneficial in the management of coronary artery disease patients. Abstract : Supplemental Digital Content is available in the text